Spectrophotometric determination of Olanzepine following condensation reaction with p-dimethylaminobenzaldehyde (2014)
A new, simple, cost-effective spectrophotometric method was developed for the determination of olanzapine in pharmaceuticals. The new method is based on formation of a yellow condensation product with p-dimethylaminobenzaldehyde, followed by measurement of absorbance at 410 nm. The reaction variables were optimized at 500C and 10 min. The reaction occurred at a stoichiometric ratio of 1:1. Absorbance was found to increase linearly with the concentration of the drug and formed the basis for quantification. The calibration graph was linear between 5 and 160 µgmL−1, and the correlation coefficient was 0.999. The apparent molar absorptivity was 0.6 ×103 L mol−1 cm−1, and the calculated Sandell sensitivity was 49.50 ng cm−2. The limits of detection and quantification were 6.6 and 20 µg mL−1, respectively. The method was validated in terms of accuracy, precision and reproducibility. The overall recovery was 98.4–101.5%, with an error of less than 1.7%. The proposed method was applied to the analysis of olanzapine in pure and dosage form and found to be of equivalent accuracy and precision to the official Indian Pharmacopoeia high-performance liquid chromatography method. There was no interference from commonly used excipients. The method could readily be adapted for use in developing countries where sophisticated equipment is not available.